2015
DOI: 10.22430/22565337.215
|View full text |Cite
|
Sign up to set email alerts
|

Desempeño de redes inalámbricas y redes industriales inalámbricas en procesos de control en tiempo real bajo ambientes industriales

Abstract: El uso creciente de las redes Ethernet en el piso de la pirámide de automatización ha hecho que muchas compañías desarrollen dispositivos para operar bajo los requerimientos característicos de este nivel, en la actualidad denominada red Industrial Ethernet, a nivel industrial se encuentra en el mercado variedad de sensores y actuadores que incorporan esta tecnología, muchos de estos equipos se venden a muy alto costo, por eso en este artículo se evaluó el desempeño de dos redes inalámbricas, una con dispositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Monsalve, Arias, and Mejia concluded that wireless networks can serve as communication systems in control applications with allowable delays of up to 50 ms. In addition, their results show a better performance of Industrial Ethernet networks over conventional networks, with differences in the RTT (Round-Trip Time) of milliseconds [4]. Monitoring environmental variables in greenhouses or crops is decisive to identify issues in the crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Monsalve, Arias, and Mejia concluded that wireless networks can serve as communication systems in control applications with allowable delays of up to 50 ms. In addition, their results show a better performance of Industrial Ethernet networks over conventional networks, with differences in the RTT (Round-Trip Time) of milliseconds [4]. Monitoring environmental variables in greenhouses or crops is decisive to identify issues in the crop yield.…”
Section: Introductionmentioning
confidence: 99%